Schismatoglottideae (Araceae) of Borneo LXXVI — Two new Burttianthus species from Sarawak - Wong, Sin Yeng; Michael, Lo; Peter C., Boyce (Firenze University Press, 2023)
Two new species of Burttianthus are described from Sarawak: B. rejangicus from the Rejang and Balleh rivers of the western Rejang Basin, and B. solus from the Similajau Basin, Bintulu. Both novelties are illustrated from living plants and the spadices of eight of the nine Burttianthus species are compared in accompanying figures.